Adsorption of Arsenite by Six Submerged Plants from Nansi Lake, China. (13th November 2014) - Zhang, Zhibin; Sun, Yulin; Sun, Cuizhen; Wang, Ning; Zhang, Yanhao
Abstract : Nansi Lake is the largest and the most important freshwater lake in north China for the South-North Water Transfer Project. Due to long-time and large-scale fish farming of history, the excess fish food and excretion usually release pentavalent arsenic, which is converted into trivalent arsenic (As (III)) in the lake sediment and released into lake water. Adsorption of arsenite using six submerged plants ( Mimulicalyx rosulatus, Potamogeton maackianus, Hydrilla, Watermifoil, Pteris vittata, and Potamogeton crispus ) as adsorbing materials was investigated. The experimental data obtained have been analyzed using Langmuir, Freundlich, and Dubinin-Radushkevich isotherm models and the pseudo-first-order, pseudo-second-order, and intraparticle diffusion kinetics models. According to the results, the As (III) equilibrium data agreed well with the Freundlich isotherm model. The adsorption capacity of the plants was in the following order: Potamogeton crispus > Pteris vittata > Potamogeton maackianus > Mimulicalyx rosulatus > Hydrilla > Watermifoil . The sorption system with the six submerged plants was better described by pseudo-second-order than by first-order kinetics. Moreover, the adsorption with Potamogeton crispus could follow intraparticle diffusion (IPD) model. The initial adsorption and rate of IPD using Potamogeton crispus and Pteris vittata were higher than those using other plants studied.